INTEGRATED EDUCATION ON HEALTHY FAMILY MANAGEMENT ON THE STATUS OF DIABETIC MELLITUS PATIENTS - Shindi Hapsari; Susi Nurhayati; Nurul Khusna (Universitas Karya Husada Semarang, 2024)
Insufficient pancreatic insulin production or ineffective use by the body is the main cause of diabetes mellitus. Insulin sugar is regulated by hormones. In the initial survey, five diabetes mellitus sufferers (50%) were asked and, five of them did not understand the problem, underwent routine physical examinations, but did not regularly take the prescribed medication because they lacked family support and did not understand how serious the disease was. Objective: To determine the health status of diabetes mellitus patients in the Guntur 2 Community Health Center working area and analyze healthy family management with integrated education. Method: Purposive sampling was used in a quasi-experimental two-group pre-procedure with a sample size of 20 participants. The health status of the respondents was recorded in the observation sheet after the integrated education on diabetes mellitus was carried out as stated in the Healthy Family Assistance Book. Statistical test using the Paired T-test Results: Independent sample test results were obtained with a p-value of 0.003 and paired T-test findings with p-values of 0.001 and 0.05 respectively. Conclusion: Diabetes mellitus sufferers in the Guntur II Health Center Working Area have significantly different health statuses.